Noninvasively Collected Fecal Samples as Indicators of Multiple Pesticide Exposure in Wild Birds. (29th December 2021) - Esther, Alexandra; Schenke, Detlef; Heim, Wieland
Abstract: Pesticide use poses a potential hazard to wild birds that use agricultural farmland as their foraging habitat. Whereas most current pesticide studies have found residues in liver samples and single active substances, noninvasive sampling methods and data on a wide variety of agrochemicals are needed to determine pesticide exposure of living wild birds for postregistration monitoring. We collected feces during autumn migration of Eurasian skylarks ( Alauda arvensis ), a species that commonly forages in winter cereal crops. Birds were kept in paper bags until we measured their body condition, individually marked and released them. We analyzed the feces dropped in paper bags for the presence of 80 pesticides including rodenticides and degradation products. Nine active substances from fungicides and herbicides commonly used in grain and maize fields were detected individually, or in combination, in 25% of the samples. We found no significant differences in body condition between exposed and unexposed birds, but Eurasian skylarks without pesticide residues had a better body condtion score on average than birds with pesticide residues. Pesticide determination in noninvasively collected fecal samples allows a refined risk analysis, which takes pesticides used in the habitats of birds into account. It allows the search for the sources of pesticide contamination, but also enables research into potential deleterious effects on the fitness of farmland birds. Environ Toxicol Chem 2022;41:201–207. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.